4-Hydroxy-2-nonenal Induces Apoptosis by Inhibiting AKT Signaling in Human Osteosarcoma Cells - Guang-rong Ji; Nai-chun Yu; Xiang Xue; Zong-guang Li (The Scientific World Journal)
The onset of lipid peroxidation within cellular membranes is associated with changes in their physiochemical properties and enzymatic dysfunction of the membrane environment. There are increasing bodies of evidence indicating that aldehydic molecules generated endogenously during the process of lipid peroxidation are causally involved in most of the pathophysiological effects associated with oxidative stress in cells and tissues. 4-Hydroxy-2-nonenal (4-HNE), among them, is believed to be largely responsible for cytopathological effects observed during oxidative stress in vivo and has achieved the status of one of the best recognized and most studied of the cytotoxic products of lipid peroxidation. Here, we reported that 4-HNE treatment may induce cell death in MG63 human osteosarcoma cells. The 4-HNE treatment could activate caspase-3 and alter the Bax/Bcl-2 apoptotic signaling. All these changes are due to the inhibition of AKT activity by 4-HNE treatment, and we also found that the p70S6K activity, downstream factors of AKT, was also blocked by 4-HNE. Our results revealed the molecular mechanism of how 4-HNE induces cell death in MG63 human osteosarcoma cells, which contributes to the clinical treatment of cancer therapy.